Policy recommendations for digital banking development contributing to sustainable development in Vietnam - Nga Phan Thi Hang (Cogent Business & Management, 2024)
The prolonged period of the COVID-19 epidemic has dramatically impacted the lives of every individual globally, giving rise to social risks and affecting all aspects of operations, including banking activities. Because direct transactions cannot be made, customers must go through the Internet to make their transactions. The Internet creates many channels for consumers to participate in transactions, interact with banks, and conveniently use financial services. This leads to consumers' habits shifting from offline to online and non-cash payments. This shifting trend pushes banks to change to meet customer needs and the widespread deployment of mobile banking, online banking, and digital banking to satisfy requirements and increase customer experience while competing with financial technology companies. Thus, the article's goal is to explore critical factors affecting digital banking development, and from that, the author gave policy recommendations for developing digital banking in Vietnam. Based on the article's goal, the researchers utilized a combination of qualitative and quantitative methodologies with a sample size of 350 managers related to 10 commercial banks in Hanoi and Ho Chi Minh City using SPSS 20.0 and Amos to process the data survey. The study's contributions help policymakers and banking managers apply research results to develop six policy recommendations for digital banking, an inevitable trend of commercial banks today. The research results also analyzed the significant advantages, difficulties, and challenges. The research paper has presented some advantages, pointed out some problems and difficulties that Vietnamese commercial banks face, and proposed policy recommendations for digital banking and sustainable development.
Keywords: 650; Digital; banking; sustainable development; policy; Vietnam